The Role of Healthcare Chaplaincy in Restoring the Spiritual Dimension of Clinical Mindfulness: A Conceptual Framework - Chandi Bhandari (Journal of Evidence-Based Medical Research, 2026)
Background: Mindfulness-based interventions are embedded across mental health, primary care, oncology, pain management, and supportive care. Their clinical translation has produced therapeutic benefits but has also encouraged a predominantly technique-oriented model in which attention regulation and symptom reduction may become separated from questions of meaning, moral orientation, worldview, suffering, transcendence, and relationship. These dimensions are not universally religious, yet they often constitute the spiritual context through which patients interpret illness and contemplative practice. Aim: This paper develops a conceptual framework for the chaplain's role in recovering the spiritual dimension of clinical mindfulness while preserving clinical evidence, patient autonomy, cultural humility, and professional boundaries. Methods: A theory-informed conceptual synthesis was undertaken using recent literature published from 2019 onward concerning mindfulness-based interventions, meditation-related adverse effects, spirituality in healthcare, spiritual care, chaplaincy outcomes, interdisciplinary practice, and culturally responsive mindfulness. Concepts were integrated through iterative comparison of mindfulness mechanisms, spiritual-care functions, chaplain competencies, and clinical safety requirements. Results: The proposed Chaplain-Integrated Spiritual Mindfulness (CISM) Framework contains seven interdependent constructs: spiritual receptivity, worldview congruence, meaning coherence, ethical congruence, relational-transcendent connection, spiritual struggle, and integrative safety. The chaplain contributes through spiritual assessment, interpretive dialogue, meaning reconstruction, tradition-sensitive translation, ethical discernment, compassionate presence, and interdisciplinary referral. A staged clinical pathway and seven testable propositions link chaplain involvement to engagement, spiritual well-being, coping, treatment congruence, and safety. Conclusions: Chaplaincy can enrich clinical mindfulness without re-religionizing healthcare or replacing mindfulness clinicians. Its distinctive contribution is contextual: helping patients determine what mindfulness means within their own worldview, values, relationships, suffering, and sources of transcendence. The framework provides a basis for interdisciplinary implementation and empirical testing of spiritually responsive mindfulness care.